The Formulation of a Body Scrub Combining Sweet Orange Peel (Citrus x sinensis L.) and Coconut Dregs (Cocos nucifera L.) as an Antioxidant - Riziek, Habieb; Arrahman, Ghery; Savitri, Anita; Zahara; Hanifah, Risa; Maharini, Indri; Efendi, M. Rifqi (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2024)
The sweet orange peel (Citrus x sinensis L.) possesses antioxidant properties that can be harnessed for developing a pharmaceutical preparation based on natural ingredients, particularly in skin care products such as body scrubs. Meanwhile, coconut pulp (Cocos nucifera L.) has a textural quality that lends itself to use as a scrubbing agent, capable of removing dead skin cells. This study aimed to ascertain the antioxidant activity of body scrub formulations with varying concentrations of extract. The results of the phytochemical screening indicated the presence of alkaloids, flavonoids, tannins, and triterpenoids. Three formulations of body scrub were prepared, designated FI (1.25% extract), FII (2.5% extract), and FIII (5% extract). The results of the physical tests demonstrated that the organoleptic, pH, spreadability, and adhesion tests met the requisite standards. In the antioxidant activity test with the DPPH reagent, the IC50 value of each formula is as follows: The results demonstrated that the IC50 value of each formula was 7.28 ppm (very strong) for FI, 11.839 ppm (very strong) for FII, and 17.354 ppm (very strong) for FIII.